Assessment of the Adoption Rate of Technologies among Fadama III Farmers in Adamawa State, Nigeria - AdamuMadu, Umar (Asian Journal of Agriculture and Rural Development, 2013)
The study was conducted in Adamawa State, Nigeria. The major thrust of this study is to assess the adoption rate of technology in Fadama III. In its four years of operation, Fadama III project has realized significant impact on household access to new and proven technologies. Adoption rate of technologies among beneficiaries has increased from 43.75% before the inception of the project to 96.255% after the project intervention. This indicates 50% increase against only 20% increase among the non-beneficiaries. Adoption rate of off-farm technologies (agricultural marketing and financial management) was also large. The adoption rate for the all the technologies was significant at p = 0.05, except for fish feed formulation, Cold storage, marketing and fish smoking. Yields among respondents have increased significantly due to adoption of proven technologies. The increase was higher among crop farmers (59.38%) followed by livestock farmers (48.75%). The increase in yields across all the enterprises has exceeded the set target of 20% increase except for fish production (11.25%) and Agro-forestry (6.88%). The increase was more among the beneficiaries compared to non-beneficiaries. It can be concluded that project did not only influence the beneficiaries to adopt technologies for the purpose of improving their socio-economic status but it has also influenced the non-beneficiaries living in Fadama III communities to adopt technologies. Fadama III needs to harmonize existing approaches and need to use complementary systems rather than conflicting ones.